2013
DOI: 10.4238/2013.april.25.8
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 and CD86 genetic variants and haplotypes in patients with rheumatoid arthritis in southeastern China

Abstract: ABSTRACT. The cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and costimulatory molecule (CD80/CD86) genes are important susceptibility genes associated with autoimmune diseases. CTLA-4 polymorphisms have been found to be associated with various autoimmune diseases. However, the association data are inconsistent for rheumatoid arthritis (RA). We investigated the genetic association of CTLA-4 and CD86 polymorphisms with RA in a Chinese population. Four single nucleotide polymorphisms (SNPs) (rs5742909 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…On the other hand, our study failed to show any association between CTLA4 + 49 A/G and CD86 +2379G/C variants and brucellosis risk. In agreement with our findings, these SNPs have not been associated with risk of COPD , RA , or systemic sclerosis . However, these polymorphisms have been shown to be associated with primary biliary cirrhosis and hepatitis B infection .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, our study failed to show any association between CTLA4 + 49 A/G and CD86 +2379G/C variants and brucellosis risk. In agreement with our findings, these SNPs have not been associated with risk of COPD , RA , or systemic sclerosis . However, these polymorphisms have been shown to be associated with primary biliary cirrhosis and hepatitis B infection .…”
Section: Discussionsupporting
confidence: 92%
“…Among which, 16 studies were irrelevant. At last, a total of 27 eligible independent case–control studies in 24 articles were included [9-33]. The characteristics of selected studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles were excluded because 2 were review articles, 1 contained duplicate data, and 1 had no data concerning the polymorphisms. Thus, 19 studies met our inclusion criteria [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. They consisted of 8 studies on the CTLA-4 polymorphism with 2093 patients and 2480 controls, 5 on the CD226 polymorphism with 2278 patients and 1940 controls, 6 on the FAS polymorphism with 546 patients and 618 controls, and 3 on the FASL polymorphism with 321 patients and 307 controls (Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…While some studies have found that CTLA-4 rs5742909, CD226 rs763361, FAS-670 rs1800682, and FASL rs763110 polymorphisms are associated with RA, other studies have reported no such association [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. To overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false positive or false negative associations [32][33][34], we performed a meta-analysis to determine whether these polymorphisms are associated with RA susceptibility.…”
Section: Introductionmentioning
confidence: 95%